Analisis Kesulitan Guru dalam proses pembelajaran menggunakan pembelajaran Online - Anggraito, Dewoso; S P, Jenny Indrastoeti; Matsuri, Matsuri (Jurnal Pendidikan Dasar, 2021)
Analysis of online learning difficulties experienced by teachers at SD N Karangasem IV Surakarta. The purpose of this study is to describes the online learning difficulties experienced by teachers in the learning process which includes preparation and implementation. This research is a qualitative research with the type of qualitative research descriptive method. Sources of data and data come from teachers, totaling 6 teachers, namely teachers in grades I - VI. Data collection techniques using questionnaires, and document studies. Validity test technical triangulation used. Data analysis using interactive analysis techniques Milles and Huberman. The results showed that the difficulties experienced by online learning by teachers were the difficulties of teachers in the preparation stage of preparing lesson plans, while at the implementation stage there were several difficulties experienced by teachers, namely the selection of learning media, selection of methods, delivery of materials and evaluation of online learning.